Coxiella burnetii in domestic doe goats in the United States, 2019–2020 - Miller, Halie K.; Branan, Matthew; Priestley, Rachael A.; Álvarez-Alonso, Raquel; Cherry, Cara; Smith, Cody; Urie, Natalie J.; Wiedenheft, Alyson; Bliss, Clayton; Marshall, Katherine; Kersh, Gilbert J. (Frontiers in Veterinary Science, 2024)
Coxiella burnetii is a bacterial pathogen capable of causing serious disease in humans and abortions in goats. Infected goats can shed C. burnetii through urine, feces, and parturient byproducts, which can lead to infections in humans when the bacteria are inhaled. Goats are important C. burnetii reservoirs as evidenced by goat-related outbreaks across the world. To better understand the current landscape of C. burnetii infection in the domestic goat population, 4,121 vaginal swabs from 388 operations across the United States were analyzed for the presence of C. burnetii by IS1111 PCR as part of the United States Department of Agriculture, Animal Plant Health Inspection Service, Veterinary Services’ National Animal Health Monitoring System Goats 2019 Study. In total, 1.5% (61/4121) of swabs representing 10.3% (40/388) (weighted estimate of 7.8%, 95% CI 4.4–13.5) of operations were positive for C. burnetii DNA. The quantity of C. burnetii on positive swabs was low with an average Ct of 37.9. Factors associated with greater odds of testing positive included suspected Q fever in the herd in the previous 3 years, the presence of wild deer or elk on the operation, and the utilization of hormones for estrus synchronization. Factors associated with reduced odds of testing positive include the presence of kittens and treatment of herds with high tannin concentrate plants, diatomaceous earth, and tetrahydropyrimidines. In vitro analysis demonstrated an inhibitory effect of the tetrahydropyrimidine, pyrantel pamoate, on the growth of C. burnetii in axenic media as low as 1 µg per mL. The final multivariable logistic regression modeling identified the presence of wild predators on the operation or adjacent property (OR=9.0, 95% CI 1.3–61.6, p value = 0.0248) as a risk factor for C. burnetii infection.